(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Quality of Life (QoL) among older adults is an important area of concern that directly affects their health status and wellbeing. This study was conducted to investigate and compare the social correlates influencing the Quality of Life (QoL) among older adults in rural and urban areas of Oyo State, Southwestern Nigeria. A comparative study of 958 older adults was conducted using a two-stage cluster sampling technique. A semi-structured, interviewer-administered questionnaire was used to elicit information on QoL and social security. QoL was assessed using a WHO QoL-BREF questionnaire. Twenty-six questions on a Likert scale of 1-5 gave a minimum and maximum obtainable score of 26 (20%) and 130 (100%), respectively. QoL was dichotomized into good or poor using an average of 3 and above (≥78/130; ≥60%) as good QoL and scores below 3 (<78/130; <60%) as poor QoL. Predictors of QoL were determined using logistic regression with level of statistical significance set at 95%. Overall, rural respondents exhibited a higher QoL (63.89 + 15.9) compared to the urban counterparts (60.76 + 13.9). Rural respondents had significantly higher QoL scores in physical health (61.58 + 17.8) than their counterparts (58.62 + 15.4) (p=0.006). Urban older adults had higher scores in psychological (62.17 ± 13.8) and social relationship wellbeing (68.33 ± 22.6) though insignificant (p=0.599 and 0.806 respectively). Some significant predictors of good Quality of Life (QoL) in the rural setting included type of marriage (monogamous: OR=1.866, 95% CI=1.162-2.998, p=0.010), possession of assets (OR=0.290, 95% CI: 0.175-0.481, p<0.001), while health ratings were significant in both rural and urban settings (Average: rural; OR=0.588, 95% CI=0.354-0.956, p=0.033*; urban; OR=0.373, 95% CI=0.181-0.767, p=0.007*) (Poor: rural; OR: 0.148, 95% CI=0.033-0.754, p=0.013*; urban; OR=0.125, 95% CI=0.042-0.369, p<0.001*). The QoL of older adults was above average while the social correlates found in the study included pensions and external financial assistance from faith-based organizations (FBOs). In order for older adults to enjoy enhanced QoL, adequate social security should be put in place for them to enjoy financial support and societal integration.